DISCONNECTING IN A CONNECTED WORLD: COMPARATIVE LEGAL APPROACH TO THE RIGHT TO DIS-CONNECT - Harlida Abdul Wahab; Rohana Abdul Rahman; Siti Zubaidah Othman; Nik Ahmad Kamal Nik Mahmod; Nurfairuz Noordin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Technology and digital world nowadays have resulted in constant connectivity at the workplace, even outside the working hours making the work boundaries become blurry. This transformation from the traditional 9 to 5 working hours to unlimited 24/7 has raised concerns about work-life balance, mental health, and employee well-being. Owing to this, the emergence of the right to disconnect as a legal and policy issue has taken place in many countries. Starting with France that introduced right to disconnect in her legislation, other European countries seemed to follow the practice and extended beyond Europe continent to countries such as Canada, Ireland and Australia, even though the approaches are diverse. This paper explores comparative legal approaches to the right to disconnect, analyzing how different jurisdictions have addressed this challenge through legislation. By examining legal frameworks in selected countries in the European countries such as France, Spain and Italy, together with Canada and Australia, this study highlights the diversity of regulatory strategies and enforcement challenges. The paper concludes with recommendations as a way forward for Malaysia in balancing business needs and employee rights in an increasingly digital world.